Bioleaching of Chalcopyrite Waste Rock in the Presence of the Copper Solvent Extractant LIX984N - Liu, Xiaohui; Li, Yuhong; Cao, Jianfeng; Zeng, Zhenshun; Liu, Xiaorong; Zhang, Ruiyong; Li, Qian; Sand, Wolfgang (Frontiers in Microbiology, 2022)
Heap bioleaching, the solubilization of metal ions from metal sulphides by microbial oxidation, is combined often with solvent extraction and electrowinning as an effective way to win copper from low-grade minerals. After solvent extraction the leaching solution is recycled usually, but the entrained organic solvents may be toxic to the leach organisms. Here Acidithiobacillus ferrooxidans, Leptospirillum ferrooxidans and Sulfobacillus thermosulfidooxidans were selected to perform bioleaching of chalcopyrite waste rock in the presence of LIX984N. The inhibitory effects have been evaluated by copper extraction, bacterial activity, number of actively Fe(II)-oxidizing cells and biofilm formation. Microcalorimetry, most probable number (MPN) determination and atomic force microscopy combined with epifluorescence microscopy were applied to accomplish the evaluation. The results show that the bioleaching by At. ferrooxidans was negatively affected, since the bacterial growth and activity as well as biofilm formation were negatively affected. L. ferrooxidans was sensitive to LIX984N and 50 mg/L of this extractant could inhibited its bioleaching completely. In the presence of LIX984N Sb. thermosulfidooxidans developed robust biofilms, but it did not improve copper extraction. With 10 mg/L LIX984N Sb. thermosulfidooxidans extracted the same amount of copper as the assay without. With 50 mg/L extractant the bioleaching aborted since Sb. thermosulfidooxidans stopped oxidizing Fe2+.